Rancang Bangun Sistem Pengukur Curah Hujan Jarak-Jauh Real Time Sebagai Peringatan Banjir Lahar Dingin - Sunarno Sunarno (Forum Teknik, 2010)
The aim of this research is to set up a sufficient system, which is used for real-time raingauge telemonitoring as the early warning system for cold lava avalanche of Mount Merapi.The system contains a remote station (transducer, Counter Timer, CPM Frequency Converter,FSK Modulator, and Tx/Rx) and a controller station (Tx/Rx, FSK demodulator, and personalcomputer).Data managements which are developed in this research are expected to be used in a realtime a rain gauge telemonitoring of Mount Merapi. The characteristics of data communicationin this system are unguided type with air as the media, asynchronous serial mode, simplex modetransmission, with audio modulation and frequency shift keying modulation. A pair of handy-transceiver was use in data transmitting with VHF/UHF wave at Amateur Radio DataFrequency (144,100 MHz and 431,125 MHz). Rainfall data changes 60 ml in 10 seconds wassent with the variation of sound frequency, started at 645 Hz with delay time 0.0168 seconds upto 2.993 Hz with delay time 0,0015 seconds.This research is expected to give valuable information for the telemonitoring systemengineering development, especially for engineers who work in the field of telemonitoringsystem and for the people who live in the Mount Merapi surroundingKeywords: telemonitoring, rain gauge, FSK, modulation